2020
DOI: 10.1002/ecs2.3089
|View full text |Cite
|
Sign up to set email alerts
|

Simulated solar panels create altered microhabitats in desert landforms

Abstract: Solar energy development is a significant driver of land-use change worldwide, and desert ecosystems are particularly well suited to energy production because of their high insolation rates. Deserts are also characterized by uncertain rainfall, high species endemism, and distinct landforms that vary in geophysical properties. Weather and physical features that differ across landforms interact with shade and water runoff regimes imposed by solar panels, creating novel microhabitats that influence biotic communi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
63
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 40 publications
(83 citation statements)
references
References 69 publications
9
63
0
Order By: Relevance
“…In general, we found that seed bank survival was significantly greater in shade microhabitats compared to runoff microhabitats and control microhabitats. Shade microhabitats within PV systems are notable for receiving less PAR and having lower soil moisture and temperatures, and we found this to be true for our experiment [ 47 ]. For example, soil moisture was consistently lowest in the shaded microhabitat after storms, and significantly so at the Caliche Pan site [ 47 ].…”
Section: Discussionmentioning
confidence: 62%
See 4 more Smart Citations
“…In general, we found that seed bank survival was significantly greater in shade microhabitats compared to runoff microhabitats and control microhabitats. Shade microhabitats within PV systems are notable for receiving less PAR and having lower soil moisture and temperatures, and we found this to be true for our experiment [ 47 ]. For example, soil moisture was consistently lowest in the shaded microhabitat after storms, and significantly so at the Caliche Pan site [ 47 ].…”
Section: Discussionmentioning
confidence: 62%
“…Global installed PV solar energy exceeded 500 GW of capacity at the end of 2018 and is projected to provide a majority of global energy reaching 30 to 70 terawatts by 2050, underscoring the importance of understanding its impact on terrestrial ecosystems [ 46 ]. The tilt of a panel effectively intercepts and diverts precipitation to its lower edge, creating an area of runoff which can be significantly greater in soil moisture than areas under the panel [ 47 ]. In shaded areas directly under a panel, Tanner et al [ 47 ] found soil temperatures were significantly cooler and photosynthetically active radiation (PAR) lower.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations